ГРАЖДАНСКОЕ ОБЩЕСТВО МОЛДОВЫ ПРОТИВ ПЫТОК - Боршевский, Андрей, Стефу Лилия (SUPREMANCE OF LAW, 2019)
No one shall be subjected to torture or to cruel, inhuman or degrading treatment or punishment (art. 5, Universal Declaration of Human Rights). Torture, according to the United Nations Convention against Torture, is: ...any act by which severe pain or suffering, whether physical or mental, is intentionally inflicted on a person for such purposes as obtaining from him, or a third person, information or a confession, punishing him for an act he or a third person has committed or is suspected of having committed, or intimidating or coercing him or a third person, or for any reason based on discrimination of any kind, when such pain or suffering is inflicted by or at the instigation of or with the consent or acquiescence of a public official or other person acting in an official capacity. No one shall be subjected to torture or to inhuman or degrading treatment or punishment (Convention for the Protection of Human Rights and Fundamental Freedoms). This article was prepared by the Institute for Democracy (Moldova). This article is funded by the European Union (European Instrument for Democracy and Human Rights). Opinions expressed in the article do not necessarily represent those of the European Union.
Keywords: NGOs; United Nations Convention against Torture; European Court of Human Rights; Moldova; Torture